Hydrogeochemical characterization of groundwater for public supply in the Northeastern portion of the Guarani Aquifer System - Carvalho Leite, Camila Marcon de (2021)
The Guarani Aquifer System (GAS) comprises one of the most important aquifers in the world due to its large water reserve and its groundwater quality. However, some regions that comprise the GAS groundwater for human supply are not thoroughly characterized on water chemistry and its relation with the local geology. This work presents the hydrogeochemical characterization of groundwater from the northeast region of the GAS used for human public supply in Sao Carlos (Sao Paulo, Brazil) based on samples from 27 deep boreholes. The groundwater exploration occurs mainly from GAS. However, it is also possible to verify the presence of the Botucatu, Piramboia, Serra Geral, Itaqueri, Adamantina, and Cenozoic sediments. Although little mineralized, there is a large ionic variability in the groundwater composition, also evidenced by spatial distribution of the electrical conductivity in the research area. These results explain four hydrochemical water types: mixed bicarbonate; calcium bicarbonate; sodium bicarbonate; and sodium fluoride, in decreasing order of representativeness. The concentration of ions in groundwater reflects the geological heterogeneity, through mineral dissolution and possible groundwater mixing. A Principal Component Analysis demonstrated that 62.7% of the total sample set variability is explained by two main factors. The first one represents 38.7% of the variability; mainly attributed to ions from minerals dissolution (HCO3-, Ca2+, Na+, Mg2+) and parameters related to this process (pH and electrical conductivity). The second group showed 24.0% of the total variability, which may be associated with anthropic activities origins, such as the presence of Cl-, N-NO3-, SO42-, F-, and K+.